2020
DOI: 10.3390/metabo10050212
|View full text |Cite
|
Sign up to set email alerts
|

An NMR-Based Approach to Identify Urinary Metabolites Associated with Acute Physical Exercise and Cardiorespiratory Fitness in Healthy Humans—Results of the KarMeN Study

Abstract: Knowledge on metabolites distinguishing the metabolic response to acute physical exercise between fit and less fit individuals could clarify mechanisms and metabolic pathways contributing to the beneficial adaptations to exercise. By analyzing data from the cross-sectional KarMeN (Karlsruhe Metabolomics and Nutrition) study, we characterized the acute effects of a standardized exercise tolerance test on urinary metabolites of 255 healthy women and men. In a second step, we aimed to detect a urinary metabolite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 87 publications
4
27
2
Order By: Relevance
“…Contrary to a previous attempt to explain the variability of CRF in the KarMeN population based on urinary metabolites [ 65 ], we were now able to identify sets of plasma metabolites that, together with clinical and phenotypical variables, contributed to a relatively good explanation of the VO 2peak in both sexes, after adjusting for age and menopausal status. In all approaches, the FM (%) entered the models as the first variable, already explaining 33.5% (females) or 42.3% (males) of the confounder-adjusted VO 2peak .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Contrary to a previous attempt to explain the variability of CRF in the KarMeN population based on urinary metabolites [ 65 ], we were now able to identify sets of plasma metabolites that, together with clinical and phenotypical variables, contributed to a relatively good explanation of the VO 2peak in both sexes, after adjusting for age and menopausal status. In all approaches, the FM (%) entered the models as the first variable, already explaining 33.5% (females) or 42.3% (males) of the confounder-adjusted VO 2peak .…”
Section: Discussioncontrasting
confidence: 62%
“…As a measure of PF, CRF was assessed by a standardized incremental exercise test on a bicycle ergometer (Ergobike medical, Daum, Fürth, Germany). All participants started pedaling at 25 Watts and the workload was then augmented by 25 Watt every 2 min until individual exhaustion, as previously described [ 65 , 67 ]. The respiratory gas exchange was measured breath-by-breath by using a cardiopulmonary exercise testing system (MetaMax 3B, Cortex, Leipzig, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the urinary metabolome can be considered complementary to the blood metabolome, since urine contains numerous end-products derived from food and drug metabolism [ 50 ]. Recent publications support the utility of urine analysis to reflect metabolomic changes following acute exercise, as analysis of urine permits confirmation of well-appreciated exercise-induced changes in metabolites related to several pathways including glycolysis (e.g., pyruvate and lactate), TCA cycle (e.g., citrate and succinate) and amino acid metabolism (e.g., alanine, taurine) [ 82 , 83 , 84 , 85 , 86 ]. In one of the earliest urinary metabolomic papers published, Kistner et al reported that within 15–30 min following an incremental cycling test, significant increases in urinary carnitine and novel urinary exercise-responsive metabolites could be observed; notably including increases in leucine derivatives methylsuccinate and 3-hydroxyisovalerate, and valine derivative 3-aminoisobutyrate.…”
Section: Metabolomic and Lipidomic Analyses Of Acute Exercise-regumentioning
confidence: 99%
“…In one of the earliest urinary metabolomic papers published, Kistner et al reported that within 15–30 min following an incremental cycling test, significant increases in urinary carnitine and novel urinary exercise-responsive metabolites could be observed; notably including increases in leucine derivatives methylsuccinate and 3-hydroxyisovalerate, and valine derivative 3-aminoisobutyrate. Increased urinary levels of these derivatives indicate branched-chain amino acid (BCAA) degradation and excretion in urine following exhaustive exercise [ 82 ]. However, an often-reported downside of metabolomic analyses in urine is that metabolite concentrations are highly influenced by hydration status and thus require normalization for water content.…”
Section: Metabolomic and Lipidomic Analyses Of Acute Exercise-regumentioning
confidence: 99%
“…Included studies were published between 2012 and 2021 (Table 1 and ESM). Fifteen studies included both female and male participants [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], and seven studies investigated male participants only [49][50][51][52][53][54][55]. One study examined adolescents [38], and the remaining 21 studies enrolled only adults (defined as participants aged > 18 years).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%